The CMSSM and NUHM1 after LHC Run 1 - Buchmueller, O. (Eur Phys J C Part Fields, 2014)
We analyze the impact of data from the full Run 1 of the LHC at 7 and 8 TeV on the CMSSM with [Formula: see text] and [Formula: see text] and the NUHM1 with [Formula: see text] , incorporating the constraints imposed by other experiments such as precision electroweak measurements, flavour measurements, the cosmological density of cold dark matter and the direct search for the scattering of dark matter particles in the LUX experiment. We use the following results from the LHC experiments: ATLAS searches for events with [Formula: see text] accompanied by jets with the full 7 and 8 TeV data, the ATLAS and CMS measurements of the mass of the Higgs boson, the CMS searches for heavy neutral Higgs bosons and a combination of the LHCb and CMS measurements of [Formula: see text] and [Formula: see text] . Our results are based on samplings of the parameter spaces of the CMSSM for both [Formula: see text] and [Formula: see text] and of the NUHM1 for [Formula: see text] with 6.8[Formula: see text] , 6.2[Formula: see text] and 1.6[Formula: see text] points, respectively, obtained using the MultiNest tool. The impact of the Higgs-mass constraint is assessed using FeynHiggs 2.10.0, which provides an improved prediction for the masses of the MSSM Higgs bosons in the region of heavy squark masses. It yields in general larger values of [Formula: see text] than previous versions of FeynHiggs, reducing the pressure on the CMSSM and NUHM1. We find that the global [Formula: see text] functions for the supersymmetric models vary slowly over most of the parameter spaces allowed by the Higgs-mass and the [Formula: see text] searches, with best-fit values that are comparable to the [Formula: see text] for the best Standard Model fit. We provide 95 % CL lower limits on the masses of various sparticles and assess the prospects for observing them during Run 2 of the LHC.